Activation of glucocorticoid receptor signaling inhibits KSHV-induced inflammation and tumorigenesis - Luping Chen; Ling Ding; Xian Wang; Yufei Huang; Shou-Jiang Gao (mBio, 2024)
ABSTRACTHyperinflammation is the hallmark of Kaposi’s sarcoma (KS), the most common cancer in AIDS patients caused by Kaposi’s sarcoma-associated herpesvirus (KSHV) infection. However, the role and mechanism of induction of inflammation in KS remain unclear. In a screening for inhibitors of KSHV-induced oncogenesis, over half of the identified candidates were anti-inflammatory agents including dexamethasone, which functions by activating glucocorticoid receptor (GR) signaling. Here, we examined the mechanism mediating KSHV-induced inflammation. We found that numerous inflammatory pathways were activated in KSHV-transformed cells. Particularly, interleukin-1 alpha (IL-1α) and IL-1 receptor antagonist (IL-1Ra) from the IL-1 family were the most induced and suppressed cytokines, respectively. We found that KSHV miRNAs mediated IL-1α induction while both miRNAs and vFLIP mediated IL-1Ra suppression. Furthermore, GR signaling was inhibited in KSHV-transformed cells, which was mediated by vFLIP and vCyclin. Dexamethasone treatment activated GR signaling and inhibited cell proliferation and colony formation in soft agar of KSHV-transformed cells but had a minimal effect on matched primary cells. Consequently, dexamethasone suppressed the initiation and growth of KSHV-induced tumors in mice. Mechanistically, dexamethasone suppressed IL-1α but induced IL-1Ra expression. Treatment with recombinant IL-1α protein rescued the inhibitory effect of dexamethasone while overexpression of IL-1Ra caused a weak growth inhibition of KSHV-transformed cells. Furthermore, dexamethasone induced IκBα expression resulting in inhibition of the NF-κB pathway and IL-1α expression. These results reveal an important role of the IL-1 pathway in KSHV-induced inflammation and oncogenesis, which can be inhibited by dexamethasone-activated GR signaling, and identify IL-1-mediated inflammation as a potential therapeutic target for KSHV-induced malignancies.IMPORTANCEKaposi’s sarcoma (KS) is the most common cancer in HIV-infected patients caused by Kaposi’s sarcoma-associated herpesvirus (KSHV) infection. Hyperinflammation is the hallmark of KS. In this study, we have shown that KSHV mediates hyperinflammation by inducing IL-1α and suppressing IL-1Ra. Mechanistically, KSHV miRNAs and vFLIP induce hyperinflammation by activating the NF-κB pathway. A common anti-inflammatory agent dexamethasone blocks KSHV-induced hyperinflammation and tumorigenesis by activating glucocorticoid receptor signaling to suppress IL-1α and induce IL-1Ra. This work has identified IL-1-mediated inflammation as a potential therapeutic target and dexamethasone as a potential therapeutic agent for KSHV-induced malignancies.